Ferroelectric switching of band alignments in LSMO/PZT/Co multiferroic tunnel junctions: an ab initio study. (17th July 2017) - Imam, M; Stojić, N; Binggeli, N
Abstract: Band alignments in ferroelectric tunnel junctions (FTJs) are expected to play a critical role in determining the charge transport across the tunneling barrier. In general, however, the interface band discontinuities and their polarization dependence are not well known in these systems. Using a first-principles density-functional-theory approach, we explore the ferroelectric (FE) polarization dependence of the band alignments in La 0.7 Sr 0.3 MnO 3 / PbZr 0.2 Ti 0.8 O 3 / Co (LSMO/PZT/Co) multiferroic tunnel junctions, for which recent experiments indicated an ON/OFF conductivity behavior upon switching the PZT FE polarization. Our results on the pseudomorphic defect-free LSMO/PZT/Co FTJs evidence a major FE switching effect on the band discontinuities at both interfaces. Based on the changes in the band alignments, we provide a possible explanation for the observed trends in the resistive switching.